2020
DOI: 10.3390/en13225983
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Different Integration Strategies of Hydrothermal Carbonisation and Anaerobic Digestion of Water Hyacinth

Abstract: Water hyacinth (WH) is an invasive aquatic macrophyte that dominates freshwater bodies across the world. However, due to its rapid growth rate and wide-spread global presence, WH could offer great potential as a biomass feedstock, including for bioenergy generation. This study compares different integration strategies of hydrothermal carbonisation (HTC) and anaerobic digestion (AD) using WH, across a range of temperatures. These include (i) hydrochar combustion and process water digestion, (ii) hydrochar diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 77 publications
6
42
0
Order By: Relevance
“…The slagging and fouling behaviour of the biomass was determined according to predictive indices: the alkali index (AI), bed agglomeration index (BAI), acid-base ratio (Rb/a), slagging index (SI), fouling index (FI) and slag viscosity index (SVI); as described previously. Indices were calculated based on the inorganic oxide content of the biomass, determined via XRF analysis; further details on the calculations can be found here [10,25]. The interpretation of each index is described in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The slagging and fouling behaviour of the biomass was determined according to predictive indices: the alkali index (AI), bed agglomeration index (BAI), acid-base ratio (Rb/a), slagging index (SI), fouling index (FI) and slag viscosity index (SVI); as described previously. Indices were calculated based on the inorganic oxide content of the biomass, determined via XRF analysis; further details on the calculations can be found here [10,25]. The interpretation of each index is described in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…E BMP values were expressed as (mL CH 4 gVS −1 ). More details on the methodology can be found here [10]. The headspaces of E BMP reactors were flushed with nitrogen before starting the test, to ensure anaerobic conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study indicated that the biochar obtained from WH pyrolysis could serve for heavy metal adsorption, and could be used for bioremediation application (Hasan et al, 2021). In addition, an integration strategy of hydrothermal carbonization (HTC) and anaerobic digestion (AD) using WH, showed that hydrochars and process waters from HTC process, could be valorized for a solid combustion fuel and biomethane production (Brown et al, 2020). Besides bioenergy, WH valorization showed its importance in the agricultural sector as well.…”
Section: Valorization Of Whmentioning
confidence: 99%
“…The first appearance of the species dates back to 1816 in Brazil. Subsequently, it was introduced as an ornamental plant to America at the end of the 1800s (Brown et al, 2020). Its appearance in Africa was in the early 1900s, and in Europe in the 1930s (Yan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%